Names of Residential Complexes: between Urbanonyms and Advertising Names - R. V. Razumov; S. O. Goryaev (Научный диалог)
The question of the “borderline” status in the onomastic space of the new for the Russian language category of proper names - names of residential complexes - is considered. The novelty of the study is seen in the fact that for the first time the onomastic status of the names of residential complexes is determined, and a comparative analysis of the two corps of such names collected in Yaroslavl and Yekaterinburg is carried out. The existing definitions are analyzed, possible terminological definitions of such proper names are developed. It is noted that these proper names are in field of meanings of term oykodomonym , but it is indicated that the names of residential complexes occupy an intermediate position in onomastic system: on the one hand, they fit into the category of urbanonyms, on the other hand, they are a form of advertising names. A new approach to the analysis of the names of residential complexes based on onomasiological grounds is proposed: the authors divide groups of names according to the degree of increasing the signs of proper name from descriptive designations to conditionally-symbolic nominations. The authors come to the conclusion that in the system of considered oykodomonyms two trends were formed: (1) embedding the name in an existing urbanisation given its identity and (2) creation of names that are not related to existing urban onomastic space. The analysis of the corps of Yekaterinburg and Yaroslavl names confirmed the border status of the considered proper names.